STRATEGI PEMASARAN POLITIK KEPALA DESA PETAHANA DALAM PEMILIHAN KEPALA DESA SIMPANG NANENG, KECAMATAN KARUSEN JANANG, KABUPATEN BARITO TIMUR - Dola Eriko; Jhon Retei Alfri Sandi (Jurusan Ilmu Pemerintahan, 2019)
Village Head Election is an implementation of the sovereignty of the people in the village in order to elect the Village Head that is direct, public, free, secret, honest and fair. Village Head Elections are held simultaneously throughout the Regency/City area. Prospective Village Heads must think of a strategy that can determine the victory to win the most votes. The Head of Incumbent Village in this research emphasizes the focus on four indicators of political marketing strategy, namely marketing of political products, political pricing, political promotion and placement. This study aims to find out how Political Marketing Strategy Incumbent Village Head in Selection Village Head Simpang Naneng, District Karusen Janang, East Barito Regency. The method used in this research using qualitative research method with descriptive approach. Based on the results of this study it is known that the Head of Incumbent Village uses all political marketing strategies that become indicators in the writing of this thesis, which is, among others, political product marketing strategy in the form of candidates along with their vision and mission, political price in the form of costs issued by candidates during village head election process, political promotion as a way to market and convey political messages to the community, and placement in the social life of the community. Head of Incumbent Village is expected to realize all political products in the form of vision and mission submitted to the community, so that the vision and mission is not only a discourse but can be seen clearly by the community. The incumbent village head is also expected to maximize the strategy even enhanced as a step toward preparing to follow the next election. Keywords: Strategy, Political Marketing, Incumbent Village Head, Village Head Election